Neotectonics of Al-Thirthar, Al-Habbaniya , Al-Razzazah Depressions, Central Iraq, by using Remote Sensing Data. - Al-Kubaisi, Manal; Al-Jarah, Omar; Abdul-Jabbar, Abdul-Khaleq (Iraqi Journal of Science, 2023)
The object of this research is to reveal the neotectonics of Al-Thirthar, Al-Habbaniya, and Al-Razzazah depressions by using remote sensing data. The age of the exposed rocks ranges from Early Miocene to Holocene. The depressions represent the west margin of the Mesopotamia Zone along its boundary with Al-Salman Zone. The lineament map contains three major groups of lineaments. Two of them are trending east-west and northeast-southwest parallel to the transversal fault systems of Iraq territory. The third group is trending northwest-southeast. The lineament groups reveal the tectonic and structural effects to the extension and the shape of the depressions. The intersection of the lineaments divided the area into small fragments which contribute to develop the depressions. Some of geomorphological landforms reveal that the neotectonics of depression area are relatively weak.